Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

How to integrate ∫(cos2x-cos2a)/(cosx-cosa)dx where a is constant

How to integrate ∫(cos2x-cos2a)/(cosx-cosa)dx where a is constant

Grade:12

3 Answers

Arun
25763 Points
3 years ago
∫(cos 2x - cos 2a) / (cos x - cos a) dx 
= ∫((2cos^2 x - 1) - (2cos^2 a - 1)) / (cos x - cos a) dx 
= ∫(2 cos^2 x - 2 cos^2 a) / (cos x - cos a) dx 
= ∫[2(cos x - cos a)(cos x + cos a)] / (cos x - cos a) dx 
= ∫2(cos x + cos a) dx 
= 2 sin x + x cos a + c.
Rakshit Puri
15 Points
3 years ago
Hsbs
 
∫(cos 2x - cos 2a) / (cos x - cos a) dx 
= ∫((2cos^2 x - 1) - (2cos^2 a - 1)) / (cos x - cos a) dx 
= ∫(2 cos^2 x - 2 cos^2 a) / (cos x - cos a) dx 
= ∫[2(cos x - cos a)(cos x + cos a)] / (cos x - cos a) dx 
= ∫2(cos x + cos a) dx 
= 2 sin x + 2x cos a + c
ankit singh
askIITians Faculty 614 Points
one year ago
= 2 sin x + 2x cos a + c= ∫2(cos x + cos a) dx = ∫[2(cos x - cos a)(cos x + cos a)] / (cos x - cos a) dx = ∫(2 cos^2 x - 2 cos^2 a) / (cos x - cos a) dx ∫((2cos^2 x - 1) - (2cos^2 a - 1)) / (cos x - cos a) dx 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free